The effectiveness of rectangular and cylindrical concrete blocks as energy dissipation structures in spillway and stilling basin - Nor Hidayah, Hamidon (2009)
Velocity of flow water in a channel will increase when there are different between water level at upstream and downstream of a channel. High velocity of flow water can be possessed by water flow in a spillway which the flow is caused by the gravitational force. A high velocity of flow water could possibly cause bad impacts such as erosion and scouring of riverbed and bank. Besides, this problem could also cause some destruction to the hydraulic structure like spillway and stilling basin. Regarding to this matter, the suitable precaution method need to be considered in order to control the high velocity of flow water. Therefore, a rectangular open channel model structure (40 cm x 60 cm) consists of spillway and stilling basin parts is constructed and used to conduct an experiment to study the performances and effectiveness of rectangular and cylindrical concrete blocks as energy dissipation structures. In this study, concrete blocks are arranged in row arrangement and various pattern of arrangements in spillway and stilling basin of a channel. The water flow depth and flow velocity are recorded and analyzed before and after locating energy dissipaters. For row arrangements, the increase in number of row and number of blocks can reduced the velocity of flow water more effectively and alternate arrangement of concrete blocks give the best result in reduction of flow velocity for various pattern of arrangements. In this study, the rectangular concrete block is proved to be more effective in reducing the flow velocity compared to the cylindrical concrete block with percentage of reduction of 73.68% for row arrangement and 75.41% for alternate pattern of arrangement.